THE DEVELOPMENT OF BRAIN-BASED LEARNING MODEL BASED ON SOCIO-SCIENTIFIC ISSUES (BBL-SSI) FOR BIOLOGY LEARNING IN SENIOR HIGH SCHOOL - Nuria Imamah Thurrodliyah; Jekti Prihatin; Ika Lia Novenda (Program Studi Pendidikan IPA FKIP Universitas Jember, 2020)
The demand for senior high school curriculum based on the 21st century requires students to have 4C skills (Communication, Collaboration, Critical Thinking, and Problem Solving, and Creativity and Innovation), but the fact is many students who are passive in the learning process so that learning outcomes and thinking skills critical is still low. Learning that can actively involve students can be done using the Brain-Based Learning (BBL) learning model which is modified with the Socio-Scientific Issues (SSI) approach. The purpose of this study is to produce a valid, practical, and effective BBL-SSI learning model to improve learning outcomes and critical thinking skills. The type of research is research and development. The stages of the development model in this study used the ADDIE model (Analyze, Design, Develop, Implement and Evaluate). This research was conducted at Pakusari Jember Public High School in the subject of class X students in the academic year 2019/2020. The average validation results for all products was 91.4 categorized as very valid. The effectiveness of learning outcomes based on the results of Normalized Gain analysis that was equal to 0.62 categorized as moderate and 0.71 categorized high. Psychomotor learning outcomes have increased every meeting, which was 79 and 83. Students' critical thinking skills also have increased each meeting, with a value of 65.12 which is categorized sufficiently and 71.36 which was categorized very well. The practicality results obtained from the teacher response questionnaire were 98 excellent categories and the student response questionnaire was 84.33 with very good categories.